Thermal and Fluid Dynamic Analysis of Compact Fin-and-Tube Heat Exchangers for Automotive Applications - Adam, A. Y.; Oumer, A. N.; Azri, Alias; M., Ishak; R., Mamat; Abdul Adam, Abdullah (EDP Sciences, 2018)
Flat tubes heat exchangers are commonly used in many industrial applications as a consequence of the distinctive geometrical characteristics of the flat tube compared with round tube. This paper aims to investigate the flow and heat transfer characteristics of laminar cross-flow forced convection in compact fin-and-flat tube heat exchangers. The experiment was performed to explore the influence of the tube inclination angle on the thermal hydraulic performance of the flat tube heat exchanger. Four flat tubes arranged in two aligned rows having the same longitudinal and transverse pitches have been examined in the range of Reynolds number between 1768.27 and 2259.46. A constant heat flux of 4169.63 W/m2 was applied at the inner surface of each flat tube. On the other hand, the numerical simulation is solved by ANSYS FLUENT for a two dimensional model with unstructured mesh and the results are compared against the experimental results. The numerical simulation results indicate that the average Nusselt number increased by 78.24 % for Reynolds number 1768.27. Besides that, for Reynolds number 1964.75 and 2259.46 the Nusselt numbers were increased by 75.89 % and 54.49%, respectively, compared to experimental results. Moreover, the pressure drop is increased 25 % and 83.38 % for both experimental and numerical simulation with respect to three Reynolds number. It was found that, the tube with 30° degree provides the higher heat transfer with Reynolds number 2259.46. This study could assist engineers in decisions regarding the application of compact fin-and-tube heat exchangers in the automotive field.